A liaison with her leading lady - James, Lotte R. (Harlequin historicals., 2024)
"Ruth Connell's beloved theater is under threat! In desperation, she approaches reclusive playwright Artemis Goode. If Artemis can write a hit, Ruth can save her troupe from financial ruin. Yet it's not just Ruth's livelihood in need of saving, but Artemis's shattered heart, too. As quickly as their personalities clash, their passion ignites! But while that leads their play toward success, it also leads Ruth closer to the end of her partnership with Artemis..."--